The Economic Impact of Weather and Climate - Richard S. J. Tol (Center for Economic Studies and Ifo Institute (CESifo), 2021)
I propose a new conceptual framework to disentangle the impacts of weather and climate on economic activity and growth: A stochastic frontier model with climate in the production frontier and weather shocks as a source of inefficiency. I test it on a sample of 160 countries over the period 1950-2014. Temperature and rainfall determine production possibilities in both rich and poor countries; positively in cold countries and negatively in hot ones. Weather anomalies reduce inefficiency in rich countries but increase inefficiency in poor and hot countries; and more so in countries with low weather variability. The climate effect is larger that the weather effect.
Keywords: D24; O44; O47; Q54; 330; climate change; weather shocks; economic growth; stochastic frontier analysis